Only Dead Metaphors Can Be Resurrected: A Review of Jill Lepore’s These Truths - George Blaustein (European Journal of American Studies)
Traditionally, U.S. history textbooks announce a civic function when aimed at U.S. readers: they exist to read America into the future, to imply a futurity for the American “experiment.” But present-day political breakdown has presented deep challenges for the familiar national narrative. Jill Lepore’s recent synthesis—These Truths: A History of the United States (2018)—is the most prominent such text to emerge in the wake of the 2016 presidential election. It represents the pinnacle of liberal nationalist historiography and will likely take its place on college syllabi inside and outside the United States. It is also the most substantial attempt in recent years to revive the national history as a serious intellectual genre. This essay takes the form of a narratological interpretation of These Truths. The book is an occasion to consider what national history is and what it is for.